2020
DOI: 10.1039/c9fo02033k
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic cross-linking of pectin in a high-pressure foaming process

Abstract: The enzyme laccase is a copper-containing oxidoreductase with the ability to oxidize a wide range of substrates, such as ferulic acid. Thus, the ferulic acid-containing sugar beet pectin (SBP) can be crosslinked through laccase-mediated oxidation. As cross-linking increases viscosity, it could be applied to stabilize SBP-containing foams. In this study, laccase-mediated cross-linking of SBP was investigated under conditions of a high-pressure foaming process. Shear, presence of CO 2 , and pressure were simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In addition, the enzyme laccase (EC 1.10.3.2), which is a multi-Cu oxidoreductase with the ability to oxidize a wide range of substrates, is combined with several Cu ions and synthesized by plants such as Arabidopsis . Hirayama et al also reported that Cu is necessary for the ethylene signaling process and found that responsive to antagonist 1 ( RAN1 ) gene it acts by delivering Cu to create functional hormone receptors in Arabidopsis . Marmiroli et al.…”
Section: Copper and Plantsmentioning
confidence: 99%
“…In addition, the enzyme laccase (EC 1.10.3.2), which is a multi-Cu oxidoreductase with the ability to oxidize a wide range of substrates, is combined with several Cu ions and synthesized by plants such as Arabidopsis . Hirayama et al also reported that Cu is necessary for the ethylene signaling process and found that responsive to antagonist 1 ( RAN1 ) gene it acts by delivering Cu to create functional hormone receptors in Arabidopsis . Marmiroli et al.…”
Section: Copper and Plantsmentioning
confidence: 99%
“…Active enzymes for injectable in situ-forming hydrogels include laccases, horseradish peroxidase (HRP), transglutaminases (TGases, protein-glutamine gamma-glutamyltransferase), tyrosinase (Tyr), and lysyl oxidase coupled with hydrogen peroxide (H 2 O 2 ) to support the reaction [61][62][63][64][65][66][67][68][69]. Enzymatic-mediated crosslinking using HRP induces the binding of aniline, phenol, and its derivative tyramine in the presence of H 2 O 2 [70][71][72][73]. Enzymaticmediated crosslinking forms strong covalent bonding, with reactions occurring in less than 10 min.…”
Section: Injectable In Situ-forming Hydrogels Prepared Via Enzyme Activitymentioning
confidence: 99%
“…port the reaction [61][62][63][64][65][66][67][68][69]. Enzymatic-mediated crosslinking using HRP induces the binding of aniline, phenol, and its derivative tyramine in the presence of H2O2 [70][71][72][73]. Enzymatic-mediated crosslinking forms strong covalent bonding, with reactions occurring in less than 10 min.…”
Section: Intratumoral Injection Using Anticancer Drug-loaded Injectable Hydrogelsmentioning
confidence: 99%
“…Aerated emulsions have widespread applications in food products including whipped cream, ice cream and aerated chocolate, due to their large specific surface area, small specific gravity, and excellent mechanical properties from liquid to solid. [1][2][3][4] Specifically, aerated emulsions reduce the calorific value and the cost while providing the desirable luxurious texture. 5,6 However, the relatively poor stability of aerated emulsions remains a major challenge due to their inherent thermodynamic instability as well as their complex structure at multiple length scales.…”
Section: Introductionmentioning
confidence: 99%